(untitled) (Polifonia, 2002)
ABSTRACT: In this paper, I present one of the possible readings of the book for teenagers Nossa rua tem um problema (Our street has a problem) by Ricardo de Azevedo, which focuses on the issueof identity and sociability of teenagers. Both verbal and non-verbal aspects are analyzed.